KECERDASAN EMOSIONAL, LINGKUNGAN KERJA, DISIPLIN KERJA DAN PRODUKTIVITAS KERJA GURU SD DI LOMBOK TIMUR - Parhanuddin, Parhanuddin; Hadiyati, Ernani; Muawanah, Umi (Universitas Hamzanwadi, 2023)
This study aimed at 1) analyzing partially the influence of emotional intelligence, work environment, and work discipline on the work productivity of Educators in State Elementary Schools in West Sakra District. 2) analyzing whether the variables of emotional intelligence, work environment, and work discipline simultaneously influence on the work productivity of Educators in State Elementary Schools in West Sakra District. 3) analyzing the variables of emotional intelligence, work environment, and work discipline, which variables had the most dominant influence on the work productivity of Educators in State Elementary Schools in West Sakra District. This study was a causal associative research. This study was also a population study where the number of respondents who returned the questionnaire was 105 respondents. Quantitative analysis technique was used in this study with the assistance of SPSS 20. This study showed that 1) Emotional Intelligence had a positive influence on the productivity of the performance of educators in State Elementary Schools in West Sakra District. 2) The work environment had a positive influence on the productivity of the performance of educators at State Elementary Schools in West Sakra District. 3) Work Discipline had a positive influence on the productivity of the performance of educators at State Elementary Schools in West Sakra District.